Sinophobia : anxiety, violence, and the making of Mongolian identity - Billé, Franck (University of Hawaiʻi Press, 2015)
This is a study of the anti-Chinese sentiments currently widespread in Mongolia. Graffiti calling for the removal of Chinese dot the urban landscape, songs about killing the Chinese are played in public spaces, and rumours concerning Chinese plans to take over the country and exterminate the Mongols are rife. Such violent anti-Chinese feelings are frequently explained as a consequence of China's meteoric economic development, a cause of much anxiety for her immediate neighbours and particularly for Mongolia, a large but sparsely populated country that is rich in mineral resources.